HUBUNGAN MANAJEMEN AKTIF KALA TIGA DENGAN INISIASI MENYUSUI DINI DI KABUPATEN SUMEDANG TAHUN 2010 - Ana, Ade; Dasuki, Djaswadi; Taufiqurahman, Irwan (IPAKESPRO, 2014)
Background: Intervention in activemanagement of the third stage of labor (AMTSL) is aimed to accelerate the deliveryof the placenta, to prevent and reduce blood loss in the third stage of labor. Early initiation of breastfeeding facilitates,a baby to start breastfeeding right away, that aims to stimulate the babyâs suckling reflex for increasingmilk production.This practice can reduce the risk of infant mortality due to hypothermia and infection in infants under 1 month. There are several obstacles in its implementation, due to policy, providers and client. It is important to implement AMTSLand early initiation of breastfeeding to improve the health of mothers and infants accordingly.Objective: To determine the implementation of activemanagement of the third stage and early breastfeeding initiationMethods: This study was an observational study with cross sectional design. The samples were 166 postpartummothers and newborns in public hospitals and health centers at District of Sumedang. Analysis of the data usedunivariate analysis, bivariate analysis using Chi-square and multivariate analysis using logistic regression.Results and Discussion:Â RThe prevalence of active management of the third stage success was 77,1 % and 48,8 %was completed with early initiation of breastfeeding. There was a significant relationship between the success ofearly breastfeeding initiation after active management of the third stage (OR= 3,1, 95 % CI= 1,12-8,49 ). Otherfactors that related were the support of providers, client support and delivery place. Less supportive policy, noten steps to successful breastfeeding and lack of trained personnel led to differences in perception. Lack of staffmotivation and clear information caused the client did not understand the importance of both these proceduresdone.Conclusion: The success of active management of the third stage and early breastfeeding initiation can be achieved ifthere was a comprehensive support from policy makers (policy side), service providers (support side) and servicerecipients (demand side)Â Â